2022
DOI: 10.3390/foods11020172
|View full text |Cite
|
Sign up to set email alerts
|

Long-Aged Parmigiano Reggiano PDO: Trace Element Determination Targeted to Health

Abstract: The concentrations of four health-related trace elements were measured using Atomic Absorption Spectroscopy in long-ripened (24- and 40-months) Parmigiano Reggiano (PR) PDO cheese, obtained from both summer and winter milk. To date, there are limited data on PR trace element concentrations, and no data about long-ripened cheese, especially when ripened for 40 months. Thus, the aim of this investigation is to determine chromium, manganese, selenium, and zinc concentrations, improving the available data on these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The concentration of elements in foods can be affected by various factors, including climate and translocation from soil, water, and air [ 19 ]. Research has shown that elemental fingerprints of dairy products can be used to discriminate their geographical origin [ 23 , 24 , 25 ], verify their PDO authenticity [ 20 , 26 , 27 , 28 , 29 ], identify breeding methods [ 30 ], assess production processes [ 31 ], and trace the production chain [ 32 ]. Accurate sampling is necessary to achieve these goals and encompass all variables that can influence the elemental fingerprint.…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of elements in foods can be affected by various factors, including climate and translocation from soil, water, and air [ 19 ]. Research has shown that elemental fingerprints of dairy products can be used to discriminate their geographical origin [ 23 , 24 , 25 ], verify their PDO authenticity [ 20 , 26 , 27 , 28 , 29 ], identify breeding methods [ 30 ], assess production processes [ 31 ], and trace the production chain [ 32 ]. Accurate sampling is necessary to achieve these goals and encompass all variables that can influence the elemental fingerprint.…”
Section: Introductionmentioning
confidence: 99%
“…Today, more than 50% of soil lacks micronutrients, which directly leads to a reduction in the crop yield and quality of agricultural products. More than 2 billion people in the world are in a state of malnutrition, and the lack of micronutrients has had an adverse impact on human health [ 2 , 3 , 4 ]. This deficiency is mainly caused by the availability of micronutrients, which cannot provide a sufficient amount necessary for plant uptake.…”
Section: Introductionmentioning
confidence: 99%
“…Santarcangelo et al [ 7 ] reported that the long-ripened Parmigiano Reggiano Italian cheese has a beneficial content of minerals, indicating that it is an interesting food source, of selenium and chromium, among the others, which have beneficial health properties according to European Regulation 432/2012. The characteristics and health-promoting properties of green banana flours have been reported in the study of Khoza et al [ 8 ].…”
mentioning
confidence: 99%